Oxidizability Enhancement of Hydroxyl Terminated Polyether Polyurethane Elastomers via Fluoroalcohols Grafting. Issue 7 (31st May 2022) - Shen, Chen; Yan, Shi; Sun, Xiaole; Tan, Yanwei; Ou, Yapeng; Jiao, Qingjie
Abstract: A series of fluoroalcohol grafted hydroxyl‐terminated polyether (HTPE) polyurethanes (PU) elastomers were synthesized by a two‐step method. The reaction progress was investigated by chemical titration and Fourier transform infrared spectroscopy (FTIR). The glass transition temperature (Tg), mechanical properties, morphology, and thermal decomposition behavior were determined for the preliminary analysis of PUs; the oxidizability property was tested by the decomposition of PU/Al composites. The results of mechanical and morphology properties demonstrated that the mechanical strength of modified PU elastomers was effectively improved for microphase separation of the hard segment. The PU film with the optimized fluoroalcohol content shows excellent performance of 17.7 MPa (tensile strength) and 547 % (elongation at break) at room temperature. Analysis of the thermal behaviors suggests that the oxidation ability of the modified PU is enhanced by the strong electronegativity of fluorine. The oxidizing gas HF, CFx, released during fluoroalcohol decomposition reacts with the alumina shell, releasing internal reactive Al, which improves the activity of the aluminum. This study might provide a new idea for utilizing high‐performance polymer binders in composite solid propellants and casting explosives. Abstract :